The experimental evaluation and improvements of a novel thermal diode pre-heat solar water heater under simulated solar conditions. (June 2018) - Smyth, M.; Quinlan, P.; Mondol, J.D.; Zacharopoulos, A.; McLarnon, D.; Pugsley, A.
Abstract: This paper presents the development through experimental performance characterisation of a pre-heat Integrated Collector Storage Solar Water Heater using a novel thermal diode operation to reduce ambient heat loss during non-collection periods. Using a solar simulator facility at Ulster University, the novel prototype pre-heat Mark IV unit was tested and evaluated. The concept has been designed and developed to be a sustainable pre-heat alternative to other types of solar water heating systems traditionally used in domestic hot water installations. The highest 6 h collection efficiency was 36.17% under solar simulated conditions. The lowest system 'U' value was 0.98 Wm −2 K −1 with no draw-off conditions. When the current prototype ICS units are compared with other conventional ICS systems, particularly in terms of thermal retention during non-collection periods, an improved performance is clearly demonstrated. The measured thermal losses were approximately 40% less than other similarly measured systems. Highlights: Experimental performance characterisation of a pre-heat ICSSWH. A novel thermal diode operation to reduce ambient heat loss during non-collection periods. Experimental evaluation via a solar simulation test facility. 6 hour collection efficiency of 36.17%. System 'U' value was 0.98 W m −2 K −1 .